Wheat yield and nitrogen use efficiency enhancement through poly(aspartic acid)-coated urea in clay loam soil based on a 5-year field trial - Yan, Peng; Dong, Xuerui; Lu, Lin; Fang, Mengying; Ma, Zhengbo; Du, Jialin; Dong, Zhiqiang (Frontiers in Plant Science, 2022)
The innovation of N fertilizer and N management practices is essential to maximize crop yield with fewer N inputs. A long-term fertilization field experiment was established since 2015 in the North China Plain (NCP) to determine the effects of the eco-friendly material poly(aspartate acid) coated urea (PN) and a control treatment (CN) with a one-time basal application method on winter wheat yield and N use efficiency at four N application rates: 0 (N0), 63 (N63), 125 (N125) and 188 (N188) kg N ha-1. The results indicated that compared to CN, PN demonstrated a significant increase in wheat yield by 9.6% and 9.2% under N63 and N125, respectively, across the three experimental years, whereas no significant (p<0.05) difference was detected under N188. Leaf area duration (LAD), crop growth rate (CGR), and dry matter accumulation (DMA) increased with increasing N rates, while PN significantly increased LAD and CGR by 5.1%-16.4% and 5.4%-64.3%, respectively, during the anthesis-ripening growth stage and DMA by 13.7% and 10.1% at N63 and N125, respectively, after the anthesis stage compared to CN. During the grain filling stage, PN significantly increased the kernel maximum grain-filling rate (Gmax) by 21.7% and the kernel weight at the maximum grain-filling rate (Wmax) by 6.7% at N125 compared to CN. Moreover, compared to CN, PN significantly improved stover and grain N content at harvest and increased NUT, NPFP, and NAE by 5.7%-40.1%, 2.5%-23.3%, and 3.9%-42.8%, respectively, at N63 - N125. Therefore, PN with one basal nitrogen fertilizer application method showed promising potential in maintaining a stable wheat yield and increasing N use efficiency with a 33% urea cut (approximately 63 kg N ha-1) compared to CN at the current wheat yield level on the NCP.